Constructivism Approaches In Efforts to Improve Students Understanding on The Round Number Operations - Syahrul Munawar (IKIP Siliwangi, 2020)
The problem in this study is how the constructivism approach can improve students' understanding of integer operations. The methodology used in this study is the Classroom Action Research Method (CAR) using the Kemis and Mc. Taggart, namely: planning, (planning), the implementation of actions (actions), observation (observation) and reflection (reflection). PTK is used through 2 cycles and 4 actions. The subject of the research was the fourth grade students of SDN 4 Galanggang, Batujajar Subdistrict, West Bandung Regency, the theory used in this study was the theory of Piaget and Brunner. Both theories are very relevant to the constructivism approach used in this study, the constructivism approach is an approach to teaching and learning that positions students as individuals who actively construct their own knowledge through experience from the surrounding environment. With the constructivism approach applied the teacher acts as a facilitator, motivator and mediator for students. Improved understanding and activity of students is shown by changes in scores and changes in the average score of students from the first cycle to the second cycle that is from 71.62 to 83.78. Besides that, an increase in student understanding and activity can also be seen from the average normalized gain of 0.36 for the first cycle to the second cycle. In addition to increased understanding, students also showed a positive response to the constructivism learning approach seen from the results of the questionnaire that most (75.67%) students gave positive responses